Cognitive computing and information processing : third International Conference, CCIP 2017, Bengaluru, India, December 15-16, 2017, Revised selected papers /: third International Conference, CCIP 2017, Bengaluru, India, December 15-16, 2017, Revised selected papers. (2018) - Unknown
No abstract available